QUALITY CONTROL CONSIDERATION: EFFICIENT REAL-TIME WATER MONITORING UTILIZING MULTI-SENSORS AND ICT CONCEPTS - Srour, T.; Haggag, Ayman; A. M., Mohsen; Saber, Ibrahim; Abou Elazm, A. E. (International Journal of Research -GRANTHAALAYAH, 2018)
Design efficient an interactive system for water pollution monitoring and quality control is proposed in this paper utilizing different sensors and employing Information Communication Technology (ICT). The presented system is built based on the pH and temperature water parameters. The system consists of sensors, Arduino controller and designed Graphical User Interface (GUI). GUI is designed to display the parameters values and control option. The operator can control the parameters values through operating control systems by a set of control switches in GUI. For example, the result of pH parameter during the monitoring = 7.06, while after operating the control system the pH parameter = 10.16. This result shows the ability of the system to monitor and control of water parameters. Different water parameters and properties are discussed in this paper also.